2012
DOI: 10.1556/aoecon.62.2012.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Government debt vs. financial depth dilemma in developing countries: The case of Turkey

Abstract: The aim of this paper is to investigate the impact of banks’ sovereign debt exposures on the financial development of Turkey. Results of the bounds test reveal a long-run and negative equilibrium relationship between banks’ domestic claims on sovereign and financial development, while Granger causality tests display a unidirectional causation from domestic debt to financial depth. Furthermore, stochastic frontier estimations provide evidence for the existence of cost inefficiency channel from government debt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These specifications assume that the coefficients γ and β 1 in equation are zero. The results are in line with previous literature (Emran and Farazi ; Ersoy ; İlgün ). There are significant crowding‐out effects of public sector credit on private sector credit.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These specifications assume that the coefficients γ and β 1 in equation are zero. The results are in line with previous literature (Emran and Farazi ; Ersoy ; İlgün ). There are significant crowding‐out effects of public sector credit on private sector credit.…”
Section: Resultssupporting
confidence: 93%
“…These variables contain too much irrelevant information to be correlated with financial development. This study uses the ratio of credit to government and state‐owned enterprises to GDP ( PUB ) as the main independent variable (similar to the work of Emran and Farazi ; Hauner ; and Ersoy ). This indicator directly measures the total amount of bank credit to the public sector, and it can demonstrate behaviour similar to the development of the banking sector.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Fourth, it seems that it should be spotted by the policy makers that Turkey needs to have more developed financial markets particularly due to the empirical findings of Köse et al (2010), who assert that a certain threshold level of financial development is necessary for financial openness to impact the growth of a country positively. To that end, fiscal incentives may be introduced to limit the increasing shares of local currency denominated domestic public debt in Turkish banks' portfolios that negatively affect financial development (Ersoy, 2011). Last but not least, the only long run causality detected in this study shows that the level of financial development attained after opening up of the financial markets stimulates FDI and net portfolio investment inflows to Turkey.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 74%
“…Previous studies show that fiscal deficit is negatively related to financial development (Alenoghena, 2015;Caballero & Krishnamurthy, 2004;Evans, 2020), while Gnimassoun & Do Santos (2021) found a positive effect. It has been confirmed that domestic debt drives down financial depth (Alenoghena, 2015;Ersoy, 2012;Hauner, 2006;Ismihan & Ozkan, 2012;Mun & Ismail, 2015;Umaru et al, 2023). However, Kutivadze (2011) found the contrary, as the author indicates that debt positively influences financial development.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Ersoy (2012) found the impact of banks' sovereign debt exposures on Turkey's financial development. The findings reveal that high domestic public debts in Turkish banks' portfolios negatively affect financial development.…”
Section: Literature Reviewmentioning
confidence: 94%